Residential exposure of electromagnetic fields radiated from mobile base stations and broadcast transmitters - Udo, E. U.; Maduka, E. B.; Okey, D. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
This paper presents the cellular base station electromagnetic radiation and its effects on human body. Due to technological advancement, human life is subjected to high level of electromagnetic emission. The effect of electromagnetic radiation (EMR) is recognized from health risk associated with exposure to it. The research work was performed in two Communication companies, namely COMPA and COMPB located in Owerri, Imo State, in two geographical areas of Onitsha – Owerri Road and Owerri Municipal. The study was conducted to ascertain power density measurement using SureCall signal meter in 72 houses within a distance of 200 - 2500 meters from the base stations. Results obtained revealed that the average cumulative power density at different distances of 200m, 500m, 800m, 1200m, 1700m, and 2500m were 1.54005627200µW/m2, 0.319382647200µW/m2, 0.171062647200µW/m2, 0.139667752800µW/m2, 0.028675447200µW/m2, and 0.001429063200µW/m2, respectively. These results were compared with International Standard and World Health Organization (WHO) allowable limits. In conclusion, it was observed that the power density varied with distance from tower and is highest at the shortest distance. Power density also varied from place to place depending on the infrastructure obstruction, like buildings or internal obstructions.